Cybercrime and Its Impact on E-Commerce Technology - Efni Yulia Santri Harahap; Nabila Ramadhani; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
This study aims to educate those who use e-commerce about the existence of cybercrime and its impact on e-commerce applications. Cybercrime is known as a cyber crime that is carried out online. One example of this is e-commerce. Those who use e-commerce already know about the effects of cybercrime on e-commerce. Predicting cybercrime remains difficult. So should be more vigilant against this crime.